Validity and reliability of the Turkish version of the Düsseldorf orthorexia scale (tr-dos) and the prevalence of orthorexia nervosa among Turkish university students - Kavsara, Hasan Kaan; Gül Koyuncu, Açelya; Dere Yelken, Handenaz; Barthels, Friederike; Stroebele Benschop, Nanette (My University, 2025)
Orthorexia Nervosa (ON) is characterized by an excessive preoccupation with healthy foods accompanied by the avoidance of self-declared unhealthy options, yet it remains unrecognized in major diagnostic guidelines. The Düsseldorf Orthorexia Scale (DOS), a 10-item self-report questionnaire using a four-point Likert scale, assesses the obsession with healthy eating. This study evaluates the reliability and validity of the TR-DOS in the Turkish context and estimates the prevalence of ON among university students. Several studies have shown that translating the DOS into various linguistic groups may exhibit different models of DOS scores. However, the psychometric properties and model fit of the DOS have not yet been investigated in Turkish-speaking populations; to address this gap, we assessed the psychometric properties of a Turkish translation of DOS (TR-DOS) in a sample of 425 university students in Türkiye. The TR-DOS revealed a 7.3% ON prevalence and a 9.0% risk of development. Weak positive associations were observed between TR-DOS total scores and BMI (r = 0.152, p =.002). Exploratory Factor Analysis confirmed the validity of TR-DOS (KMO = 0.867) with satisfactory reliability (Cronbach’s alpha = 0.854). Confirmatory Factor Analysis indicated an acceptable fit for the TR-DOS model (χ2/df = 3.127, RMSEA = 0.071, SRMR = 0.046, IFI = 0.955, CFI = 0.955, GFI = 0.956, TLI = 0.932). Moderate positive correlations were found between TR-DOS and eating disorder measures (EAT-26: r = 0.428, p <.001; EDE-Q-13: r = 0.430, p <.001). The findings demonstrated that the TR-DOS is both culturally appropriate and psychometrically adequate for Turkish university students. It is a reliable and valid instrument for assessing obsessive healthy eating behaviors in this population.
Keywords: Dusseldorf Orthorexia Scale; Eating Attitudes; Eating Disorders; Orthorexia Nervosa; Validation Studies